EFEKTIFITAS PROGRAM ONE DAY BOARDING DALAM MEMBENTUK KARAKTER ISLAMI SISWA SMP dan MTS MUHAMMADIYAH DI KABUPATEN SIDOARJO - wijayanto, anang (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
This research aims to determine the effectiveness of the One day Boarding program in forming and strengthening the Islamic character of Muhammadiyah Middle School and MTS students in Sidoarjo district. Education is the most important thing in the progress of a nation and is one of the main factors in creating a valuable and civilized life in society. The values referred to are life values that are in accordance with religious and national norms in order to strengthen the character of people's lives in general, so that from an early age all educational programs should be directed at the process of strengthening students' Islamic character which includes moral knowing, moral feeling, and moral action. The strong current of societal cultural disruption in the era of the industrial revolution 4.0 is a challenge in itself and requires extraordinary effort. This era relies on the intellectual engineering of artificial intelligence and the internet of things as well as big data which opens up unlimited space and opportunities for anyone to access information and interact virtually quickly and easily and at very low costs. The disruption society that is emerging does not only concern economic and technological aspects but also political, social, cultural, moral and even religious aspects.